Dill tablet and Ocimum basilicum aqueous extract: Promising therapeutic agents for improving cognitive deficit in hypercholesterolemic rats. Issue 12 (4th October 2020) - Mohammadali, Soheila; Heshami, Neda; Komaki, Alireza; Tayebinia, Heidar; Abbasi Oshaghi, Ebrahim; Karimi, Jamshid; Hashemnia, Mohammad; Khodadadi, Iraj
Abstract: High‐cholesterol diet (HCD) is correlated with Alzheimer's disease (AD) and impairment of memory. This study investigated beneficial therapeutic effects of Dill tablet and Ocimum basilicum (Basil) aqueous extract on hypercholesterolemia‐induced cognitive deficits and oxidative stress in hippocampus tissues of rats. Hippocampal Aβ(1‐42) level was measured. The gene expression levels of superoxide dismutase and inducible‐nitric oxide synthase were determined in hippocampus. Cognitive functions were examined and oxidative status was evaluated in serum and hippocampus. Phytochemical properties and in vitro antioxidant activity of Basil extract were assessed. HCD significantly increased serum cholesterol, induced deposition of Aβ plaque, altered hippocampus morphology, and impaired memory function, whereas receiving Basil extract or Dill tablet increased antioxidant potency in serum and hippocampus and normalized HCD‐induced deleterious effects. Basil extract and Dill tablet may exhibit their beneficial effects in AD by lowering serum cholesterol and evoking antioxidant system in the brain. Practical applications: Dill tablet and Basil aqueous extract lowered serum cholesterol in hypercholesterolemic animal models, therefore, they can be used as hypocholesterolemic agents. These edible herbs significantly retarded deposition of Aβ plaque and normalized hippocampal morphology, thus, they favorably protected hippocampus tissue from deleterious effects‐induced by hypercholesterolemia. Dill tablet and Basil aqueous extract also corrected oxide‐redox balance and normalized HCD‐induced oxidative stress to some extent and significantly improved impairments in learning and memory suggesting that these medicinal plants can be considered as surrogate therapeutic agents for the synthetic medicines in the treatment of AD and in postponement of its complications. Abstract : High‐cholesterol diet (HCD) increased serum cholesterol, induced deposition of Aβ plaque, altered hippocampus morphology, and impaired memory function, whereas receiving Basil aqueous extract or Dill tablet increased antioxidant potency in serum and hippocampus and normalized HCD‐induced deleterious effects on cognitive function. Dill tablet and Basil extract may exhibit their beneficial effects in Alzheimer's disease (AD) by lowering serum cholesterol and evoking antioxidant system in the brain.